'It's hard to grow when you're stuck on your own': enhancing teaching through a peer observation and review of teaching program. Issue 1 (2nd January 2021) - Hendry, Graham D.; Georgiou, Helen; Lloyd, Hilary; Tzioumis, Vicky; Herkes, Sharon; Sharma, Manjula D.
ABSTRACT: Rapid technological and social changes have prompted a strong focus on teaching practices in higher education. Among the assortment of programs and approaches aimed at developing teaching practices, peer review and observation of teaching remain widespread for their efficiency and potential to be transformative. Though such programs are well described in the literature, whether or how they affect practices remains under researched. This study reports on the accounts of past participants – with respect to changes in their teaching practices – in a peer review and observation of teaching program run in the Faculty of Science at a large, research-intensive university. Results from a questionnaire and interviews from several years' cohorts indicate that participants overwhelmingly believed that the program enhanced their teaching practice and that they continued to practice specific teaching strategies developed during their participation in the program. Particular features of the program were associated with its success, such as the role and experience of the 'reviewer' and the review cycle. The program was thought to have changed the perspective of participants in the way they think about teaching.